Peningkatan motivasi belajar melalui Digital Game-Based Education: Pendampingan guru sekolah dasar melalui program PkM - Arita Marini; Endang Wahyudiana; Juhana Sakmal; Nastitisari Dewi; Muliati Mursak; Leola Dewiyani; Desy Safitri (LPPI UMN AL WASHLIYAH, 2025)
This Community Service Program (PkM) aims to assist elementary school teachers in implementing digital game-based education as an effort to increase students' learning motivation while also creating more effective, interactive, and meaningful learning experiences. Through this approach, students are not only encouraged to be more active but are also trained in critical thinking, problem-solving, and teamwork skills, which are highly essential in the 21st century. To ensure optimal implementation, teachers need to have a solid understanding and specific skills in designing and adapting educational games in accordance with the applicable curriculum. Therefore, intensive training and mentoring are key elements in teacher empowerment. The implementation of this program at SD Al Ashriyyah Nurul Iman Islamic Boarding School has shown significant improvements in pedagogical skills, digital literacy, and teacher creativity, ultimately supporting the creation of a more innovative and sustainable learning environment. Additionally, teachers have begun to evaluate the effectiveness of the educational games used and adapt them to suit students’ learning needs. The use of various digital platforms such as Kahoot, Wordwall, and Scratch Jr has enriched the diversity of learning methods. Teachers have also started forming peer-sharing communities to support each other in implementing this method. It is expected that this mentoring model can be replicated in other elementary schools as a strategy to strengthen teachers’ capacity in facing the challenges of digital education.